PENGARUH KECERDASAN EMOSIONAL DAN KEPERCAYAAN DIRI TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI - Zahra Fazhira; Gugum Gumilar; Kurniawan Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of Emotional Intelligence and Self-Confidence on Academic Achievement in Economics at SMA Negeri 6 Tasikmalaya. The research is quantitative, utilizing descriptive analysis and multiple linear regression methods. The primary data used in this study was obtained through questionnaires distributed to 118 respondents. The results indicate that: 1) There is a significant effect of Emotional Intelligence on Academic Achievement, with a significance value of 0,000 < 0,05. 2) There is a significant effect of Self-Confidence on Academic Achievement, with a significance value of 0,031 < 0,05. 3) There is a significant influence of emotional intelligence and self-confidence on students' academic achievement, as evidenced by the calculated F value of 56.492 being greater than the F-table value of 3,07, with a significance value of 0,000 < 0,05.